2008
DOI: 10.1002/jsfa.3139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilisation levels on melon fruit quality at the harvest time and during storage

Abstract: BACKGROUND: The quality of melon fruit depends upon many factors that can be affected by growing conditions and post-harvest management. The aim of this work was to investigate the effect of nitrogen fertilisation levels on the fruit quality at harvest time and during storage. Experiments were performed in an open field using melon plants (Cucumis melo L. Var. Reticulatus cv. Prodigio). The nitrogen (N) was applied through fertigation using four fertilisation levels: 0, 55, 110 and 165 kg ha −1 . After harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 18 publications
6
24
0
1
Order By: Relevance
“…Thus, it is assumed that the low level of calcium in the organic solutions did not affect the antioxidant capacity of the organic melons that were produced. There is evidence that the application of different levels of the macronutrient nitrogen via fertigation does not affect the phenolic content of melon fruits obtained under open field conditions (Ferrante et al, 2008). Other researchers have reported that the production of nitrogen-containing compounds, such as amino acids, proteins and alkaloids, increases in crops under production systems with a sufficient nitrogen supply (Hallmann and Rembiałkowska, 2012).…”
Section: Analytical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is assumed that the low level of calcium in the organic solutions did not affect the antioxidant capacity of the organic melons that were produced. There is evidence that the application of different levels of the macronutrient nitrogen via fertigation does not affect the phenolic content of melon fruits obtained under open field conditions (Ferrante et al, 2008). Other researchers have reported that the production of nitrogen-containing compounds, such as amino acids, proteins and alkaloids, increases in crops under production systems with a sufficient nitrogen supply (Hallmann and Rembiałkowska, 2012).…”
Section: Analytical Testsmentioning
confidence: 99%
“…An alternative that has been used to manipulate the synthesis of antioxidants and phytochemical compounds in vegetable produce is the application of organic fertilizers (Benavides-Mendoza, 2002), including organic nutrient solutions, such as compost and vermicompost teas (PreciadoRangel et al, 2011). Moreover, it is known that the most efficient practice for supplying fertilizer is through the irrigation water (fertigation) as a nutritional solution (Ferrante et al, 2008). However, these nutritive solutions must be diluted to avoid phytotoxicity, thereby reducing the nutrient supply, which may represent an additional stress for growing plants.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that the fruit quality was affected adversely by excess N, resulting in fruits with a large seed cavity and therefore with small edible parts and greater skin thickness. The N application and N content in the fruit and whole plant were not correlated with the flesh firmness or TSS, in agreement with Ferrante et al (2008). Rodríguez et al (2005) found no changes in the sugar content of Galia melon when they increased N fertilizer from 80 to 240 mg L -1 and Kirnak et al (2005) stated that N application generally has little or no effect on the TSS.…”
Section: Yield Yield Components and Qualitymentioning
confidence: 59%
“…Other authors have found no significant effect of N in antioxidant activity of other crops, such as melons (FERRANTE et al, 2008) and watercress (KOPSELL et al, 2007). Nevertheless, Ibrahim et al, (2012) have reported the reduction of antioxidant activity of leaves, stems, and roots from a medicinal plant (Labisia pumila Blume) with an increase in N supply.…”
Section: Resultsmentioning
confidence: 97%